Influence of pre-treatment on the compartibility of maize cob cement mixture (2011)
The effects of pre-treatment: aqueous extraction, addition of 3% calcium chloride (CaCl2) and combination of aqueous extraction and 3% CaCl2 on maximum hydration temperature (Tmax), setting time(tmax) and time ratio indices (tR) of locally sourced maize cobs mixed with portland cement were investigated. Aquenous extraction reduced the tmax, Tmax and tR while chemical treatment and combination of aquenous extraction and chemical treatment reduced tmax and tR but increased Tmax of the maize cob-cement mixes. Generally, untreated maize cobs were moderately suitable for cement bonded composites production. Pre-treatment with 3% CaCl2 improved the compartibility of maize cobs with cement than either aquenous extraction or combined treatment with aquenous extraction and addition of 3% CaCl2. The result of this work showed that utilisation of maize cob for composite production can serve as avenues for creation of waste to wealth and thus cushion the over-exploitation of timber-resources.